The Dilemma of Postmodern Business Ethics: Employee Reification in a Perspective of Preserving Human Dignity - Vveinhardt, Jolita (Frontiers in Psychology, 2022)
Management practices prevailing in business organizations receive considerable criticism for often treating the employee as one of many resources or an instrument to achieve the organization’s goals. As employee reification has so far been largely investigated in the scientific literature from the perspective of neo-Marxist approach, this article seeks to broaden the discussion by showing how social teaching of the Catholic Church can serve to solve the problem of reification. Although there is no doubt that universal norms of business ethics can serve as protection of the employee dignity from the individual’s reification tendencies, moral relativism operating in postmodern life tends to call into question any universal moral norms. Therefore, this article discusses how responses to challenges posed by moral relativism can be obtained by applying methodological approaches proposed by the neo-Marxist classics Lukács, Honneth, and Catholic Social Teaching. The similarities and differences of these approaches are identified, and attention is also drawn to the possibilities and limitations of their application in business ethics practice. It is also demonstrated how understanding of human dignity and the attitude to a virtue, offered by social teaching of the Catholic Church, broadens the discussion on addressing the dangers posed by the person’s reification in organizations.